ANALISIS PERBANDINGAN TINGKAT KEPATUHAN TERHADAP PERSYARATAN PENGUNGKAPAN PSAK KONVERGENSI IFRS DENGAN METODE DIKOTOMUS DAN METODE PC PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Hesti Melia Fitri; Faisal Faisal (Diponegoro Journal of Accounting, 2017)
This study aims to measure the disclosure compliance level against PSAK convergence to IFRS by using two approaches, the dichotomous method (Cooke’s method) and the alternative but rarely used, the PC method. This study also aims to highlight the differences and implications of any differences between those two methods.This study is conducted by calculating the disclosure compliance level against PSAK convergence to IFRS in manufacturing companies listed in BEI by using the dichotomous and PC method. The results are then compared by using univariate statistic analysis.The results show that the disclosure compliance level in Indonesia’s manufacturing companies by the year of 2015 are 73,9% in dichotomous method and 71,4% in PC method with significantly different results between the two methods.